The Internal Structure and Dynamics of Jupiter Unveiled by a High‐Resolution Magnetic Field and Secular Variation Model. Issue 15 (11th August 2022) - Sharan, S.; Langlais, B.; Amit, H.; Thébault, E.; Pinceloup, M.; Verhoeven, O.
Abstract: Unique information about the dynamo process acting at Jupiter can be inferred by modeling and interpreting its magnetic field. Using the fluxgate magnetometer measurements acquired during the 4 years of the Juno mission, we derive a magnetic field model which describes simultaneously the main field and the secular variation (SV) up to spherical harmonic degrees 16 and 8, respectively. Apart from the Earth's, this is the first time another planetary magnetic field along with its time variation is described to such a high degree. We use properties of the power spectrum of the static field to infer the upper boundary of the dynamo convective region at 0.830 ± 0.022 Jupiter radius. The SV and correlation times are relatively comparable to the Earth's and indicate that the field is dominated by advection. The field and SV morphologies suggest zonal as well as non‐zonal deep fluid motions. Plain Language Summary: The interior of Jupiter can be described broadly as a dense core surrounded by fluids, dominantly hydrogen and helium. The hydrogen‐rich metallic fluid generates the strongest planetary magnetic field in the Solar System. Modeling and interpreting this field gives essential information about the dynamo process inside Jupiter. We use the Juno mission data throughout 4 years (or, 28 orbits) to derive an internal magnetic field and secular variation (SV) model using spherical harmonic functions. We compute a magnetic field model to degree 16 for its static part, and model its temporal variation to degree 8. The power spectrum of the magnetic field model is used to investigate the radius of the dynamo region. We infer that the convective region has an upper boundary at 0.830 ± 0.022 Jupiter radius. The strength of the annual change of field is relatively comparable to the Earth's. The slope of the SV timescales indicates that the dynamo is dominated by advective effects. The SV displays a maximum near the equator with a bi‐polar structure in agreement with zonal drift of the Great Blue Spot. However, numerous small scale SV structures suggest that the flow at the interior is complex involving both zonal and non‐zonal features. Key Points: Magnetic field of Jupiter is modeled from Juno's first 4 years of observations A degree 16 magnetic field model and degree 8 secular variation model are derived The model indicates a dynamo not far from the surface and complex motions deep inside Jupiter